NEXTMap Europe: DEM ad alta percisione dell'Europa occidentale (GEOmedia, 2009)
NEXTMap Europe's Western Europe high precisione DEMsIntermap Technologies has digitally remapped Western Europe to an unprecedented degree of uniform accuracy. Its NEXTMap  Europe database, providing three-dimensional coverage for 2.4 million square kilometers of Western Europe with a vertical accuracy of 1 meter or better for each country, is an alternative to imprecise and outdated maps. NEXTMap Europe includes digital  elevation models and orthorectified radar images that support commercial applications within the GIS, engineering, automotive, consumer GPS device, insurance risk assessment, oil and gas, hydrology, environmental planning, wireless communications, transportation, aviation, and 3D visualization markets.